Improving Awareness Could Transform Outcomes in Degenerative Cervical Myelopathy [AO Spine RECODE-DCM Research Priority Number 1]. Issue 1 (February 2022) - Davies, Benjamin M.; Mowforth, Oliver; Wood, Helen; Karimi, Zahabiya; Sadler, Iwan; Tetreault, Lindsay; Milligan, Jamie; Wilson, Jamie R. F.; Kalsi-Ryan, Sukhvinder; Furlan, Julio C.; Kawaguchi, Yoshiharu; Ito, Manabu; et al.
Study Design: Literature Review (Narrative) Objective: To introduce the number one research priority for Degenerative Cervical Myelopathy (DCM): Raising Awareness. Methods: Raising awareness has been recognized by AO Spine RECODE-DCM as the number one research priority. This article reviews the evidence that awareness is low, the potential drivers, and why this must be addressed. Case studies of success from other diseases are also reviewed, drawing potential parallels and opportunities for DCM. Results: DCM may affect as many as 1 in 50 adults, yet few will receive a diagnosis and those that do will wait many years for it. This leads to poorer outcomes from surgery and greater disability. DCM is rarely featured in healthcare professional training programs and has received relatively little research funding (<2% of Amyotrophic Lateral Sclerosis or Multiple Sclerosis over the last 25 years). The transformation of stroke and acute coronary syndrome services, from a position of best supportive care with occasional surgery over 50 years ago, to avoidable disability today, represents transferable examples of success and potential opportunities for DCM. Central to this is raising awareness. Conclusion: Despite the devastating burden on the patient, recognition across research, clinical practice, and healthcare policy are limited. DCM represents a significant unmet need that must become an international public health priority.